2004
DOI: 10.21273/hortsci.39.4.886a
|View full text |Cite
|
Sign up to set email alerts
|

Copper Fungicide Spray Timings for Melanose Control in Grapefruit: Comparison of Computer Modelling of Copper Residues vs. Calendar Sprays

Abstract: Grapefruit are susceptible to melanose from initial set until fruit diam. is 6-7 cm, which can span 3 months. Common Indian River melanose-control practice has been application of Cu fungicides at petal fall, with reapplication every three wks. through the infection period. Research data were previously used to develop a computer model to estimate Cu levels on fruit and indicate when reapplication is needed to prevent potential infection. The purpose of this study was to compare melanose control using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the case of serious infection in late summer, additional protectant spray should be applied [140]. Applications of pyraclostrobin to the spring flush growth of citrus trees are much more efficient for controlling melanose, scab, and Alternaria brown spot than those of famoxadone or copper hydroxide [44,[141][142][143][144]. Bushong and Timmer [145] demonstrated that azoxystrobin was a highly effective preventative spray for melanose, whereas benomyl and fenbuconazole were not.…”
Section: Chemical Controlmentioning
confidence: 99%
“…In the case of serious infection in late summer, additional protectant spray should be applied [140]. Applications of pyraclostrobin to the spring flush growth of citrus trees are much more efficient for controlling melanose, scab, and Alternaria brown spot than those of famoxadone or copper hydroxide [44,[141][142][143][144]. Bushong and Timmer [145] demonstrated that azoxystrobin was a highly effective preventative spray for melanose, whereas benomyl and fenbuconazole were not.…”
Section: Chemical Controlmentioning
confidence: 99%